Культура мовлення як невід’ємний аспект курсу риторики для аспірантів - Куньч, Зоряна; Вознюк, Геннадій (Видавництво Львівської політехніки, 2017)
The article raises an relevant problem of Ukrainian culture. It outlines the main features and ways to improve personal culture of speech. Specifically, the language training of graduating students in the rhetoric сlasses is aimed to form a stable language-cultural mark to improve verbal communication skills and thus to increase the level of education, communication and professionalism of future specialist.
Keywords: українська мова; культура мовлення; мовні норми; риторика; мовленнєві навички; мовна комунікація; гуманітаризація; професіоналізм